Preservasi pengetahuan lokal mitos di Dusun Kasuran Seyegan Sleman Daerah Istimewa Yogyakarta - Wasilatul Baroroh (Berkala Ilmu Perpustakaan dan Informasi)
Introduction. This study aims to identify efforts to preserve local mythological knowledge in Kasuran Hamlet through exchange of indigenous knowledge, so that local knowledge exists.